2014
DOI: 10.1007/s12035-014-8792-8
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Pre- and Pro-regions of Transgenic GDNF Affects the Ability to Induce Axonal Sprout Growth

Abstract: Plasmids containing four GFP-tagged isoforms of the human GDNF gene, with both pre- and pro-regions (pre-pro- GDNF), with the pre- (pre-GDNF) or the pro-region (pro-GDNF) alone, and without the pre- and pro-regions (mGDNF), were used to transfect HEK293 cells (human embryonic kidney cell line). The effect of the transgenic products on the growth of processes was studied in the spinal ganglia of 14-day rat embryos. Media conditioned by the transgenic cells were used to culture explants and dissociated cells of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…34,35 Past work from our group has shown that a significant fraction of cranially grafted human stem cells ultimately differentiate along glial lineages. 16,17,20,24 36 and protect neurons from transient ischemia induced damage. 37 Other work in different stem cell-based systems has noted various beneficial effects of secreted exosome-derived GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Past work from our group has shown that a significant fraction of cranially grafted human stem cells ultimately differentiate along glial lineages. 16,17,20,24 36 and protect neurons from transient ischemia induced damage. 37 Other work in different stem cell-based systems has noted various beneficial effects of secreted exosome-derived GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…For the control we used construct with pre-pro-GDNF, which were prepared using the primers T3 (F) 5′-ATTAACCCTCACTAAAGGGA-3′ и Gdnf Bam H1 5′-TGGATCCCAGA TACACCACACCTTTTAGCGG-3′. This construct was obtained according to the protocol described elsewhere [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor (GDNF) promotes the survival and differentiation of neurons and glial cells [ 1 3 ]. This GDNF activity can be useful in the treatment of neuronal degeneration and loss of differentiation typical for a number of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations